1985
DOI: 10.1007/bf00498863
|View full text |Cite
|
Sign up to set email alerts
|

Phorbol ester, an activator of protein kinase C, enhances calcium-dependent release of sympathetic neurotransmitter

Abstract: The effect of phorbol ester, phorbol 12,13-dibutyrate, was investigated on the overflow of tritium from 3H-noradrenaline-loaded sympathetic neurons of the isolated perfused salivary gland of the rat. Stimulation (1 Hz for 60 s)-evoked overflow of tritium was enhanced by phorbol ester. A significant enhancement was seen at 1 nmol/l, which increased to a maximum level (over 4-fold) at 30 nmol/l. The spontaneous overflow of radioactivity, however, was not affected by any concentration of phorbol ester. The facili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
46
0

Year Published

1987
1987
1996
1996

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 20 publications
8
46
0
Order By: Relevance
“…Effects of the phorbol esters at the soma-dendritic area of the neurone and hence an influence on the firing rate ofthe neurone can be excluded, since in the in vitro hippocampal slice preparation noradrenergic nerve terminals are cut off from their cell bodies in the locus coeruleus. Also results from electrophysiological studies (Malenka et al, 1986) and the finding that phorbol esters enhanced only the Ca2"-dependent release of neurotransmitters (this paper and: Wakade et al, 1985;Zurgil & Zisapel, 1985) point to an activation of presynaptically located PKC. Biochemical studies have demonstrated the presence of presynaptic PKC in brain slices (Girard et al, 1985), its activation during depolarization (Wu et al, 1982) and phosphorylation of membrane proteins from nerve terminals by PKC (Wu et al, 1982).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Effects of the phorbol esters at the soma-dendritic area of the neurone and hence an influence on the firing rate ofthe neurone can be excluded, since in the in vitro hippocampal slice preparation noradrenergic nerve terminals are cut off from their cell bodies in the locus coeruleus. Also results from electrophysiological studies (Malenka et al, 1986) and the finding that phorbol esters enhanced only the Ca2"-dependent release of neurotransmitters (this paper and: Wakade et al, 1985;Zurgil & Zisapel, 1985) point to an activation of presynaptically located PKC. Biochemical studies have demonstrated the presence of presynaptic PKC in brain slices (Girard et al, 1985), its activation during depolarization (Wu et al, 1982) and phosphorylation of membrane proteins from nerve terminals by PKC (Wu et al, 1982).…”
Section: Discussionmentioning
confidence: 68%
“…Up to now all investigations with phorbol esters as activators of PKC point to the possibility of an involvement of PKC in controlling neurotransmitter release both in the central (Baraban et al, 1985b;Allgaier & Hertting, 1986;Allgaier et al, 1986b;Malenka et al, 1986;Tanaka et al, 1986;Feuerstein et al, 1987) and in the peripheral (Wakade et al, 1985;Baraban et al, 1985a) nervous system. In the present paper, the conclusion that phorbol esters enhance noradrenaline release as a result of their effect on PKC is mainly supported by three observations discussed below; the facilitatory effects of two potent PKC activators, TPA and 4P-PDB (Castagna et al, 1982), the lack ofeffects of phorbol compounds which do not activate PKC, and the inhibitory effect of the PKC inhibitor polymyxin B.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the involvement of this protein kinase in the S-I release of NA has been shown in different experimental preparations, including rabbit hippocampus (Allgaier & Hertting, 1986), cat cerebral arteries (Balfagon et al, 1989), rat salivary gland (Wakade et al, 1985) and rat atria (Ishac & De Luca, 1988). Moreover, postjunctional B2 receptor activation is linked to the PKC pathway in several tissues such as the rabbit jugular vein and circular muscle of the guinea-pig ileum (Calixto & Madeiros, 1991;1992).…”
Section: Discussionmentioning
confidence: 99%
“…The S2/S, value in the presence of PKCi (1 AM) was 87.5 ± 3.6% (n = 6) compared to the DMSO control S2/S, of 100.5 ± 8.3% (n = 8). To evaluate the potency of PKCi in inhibiting PKC, we stimulated this pathway with phorbol dibutyrate (PDBu), a well known PKC activator (Wakade et al, 1985;Allgaier & Hertting, 1986). PKCi (1 AM) significantly inhibited the facilitatory action of 0.1 gM and I 1M PDBu on the S-I outflow of radioactivity (Figure 4).…”
Section: Effect Of Pkc Inhibitor On the Facilitatory Action Of Bkmentioning
confidence: 99%
“…Phorbol esters and diacylglycerol can release hormone and other transmitters from secretory elements (Nishizuka, 1984), including nerve terminals (Wakade et al, 1985;Eusebi et al, 1986;Haimann et al, 1987;Malenka et al, 1987;Nichols et al, 1987;Shapira et al, 1987). Because this release can occur in a Caindependent way (Nishizuka, 1984;Malenka et al, 1987), it is not possible in a multicellular preparation such as a brain slice or tissue culture to exclude the possibility that PKC activators…”
Section: Discussionmentioning
confidence: 99%